Status Consistency / Inconsistency of the Status Position of Social Classes - Kuzmuk, Olga М.; Кузьмук, Ольга Миколаївна; Кузьмук, Ольга Николаевна (Східноєвропейський національний університет імені Лесі Українки, 2013)
In this article author explains the class inequality in west and east European societies. Also we compare class differences of EU and NEE countries. Summarized evaluation of aggregate social status in the context of the study of social stratification requires a certain type of cumulative assessment of the status and remuneration of a particular individual. But not always score (reward) adequate of social position. Inconsistency social position and evaluation (reward) is described the concept of «status inconsistency». In this paper we describe the social inequality and characteristic of social inequality. The main dimensions of social inequality are economic status, education, professional status and political status. Based on the data comparison we implemented generalizations that describe the differences in the nature of social inequality Western European and Eastern European societies. У цій статті пояснено класову нерівність у суспільствах Західної та Східної Європи, також здійснено порівняння класових відмінностей у відповідних країнах. Узагальнено оцінку сукупного соціального статусу в контексті вивчення соціальної стратифікації, що передбачає наявність певного типу кумулятивної оцінки статусів і винагород конкретного індивіда, однак не завжди оцінка (винагорода) адекватна соціальній позиції. Невідповідність соціальної позиції та оцінки (винагороди) описано поняттям «статусна неузгодженність». У межах цього дослідження здійснено вимірювання соціальної нерівності і її характеристик. Основними вимірами соціальної нерівності є економічне становище, освіта, професійний і політичний статус. На основі отриманих даних реалізовано порівняння та побудовано узагальнення, що описують відмінності в характері соціальної нерівності західноєвропейських і східноєвропейських суспільств.
Статусна узгодженність / неузгодженість статусних позицій соціального класу
Keywords: social inequality; social class; social status; class scheme; status inconsistency; соціальна нерівність; соціальний клас; класова схема; статусна неузгодженість